Una aproximación a la transición del capitalismo al postcapitalismo - Vargas Hernández, José (2006)
This essay tries to contribute to the discussion on post capitalism from a historical standpoint. We analyse the characteristics and variables that impact the process of transition from capitalism to post capitalism.